Prognostic accuracy of day versus night ambulatory blood pressure: a cohort study - Boggia, José; Li, Yan; Thijs, Lutgarde; Hansen, Tine W; Kikuya, Masahiro; Björklund-Bodegård, Kristina; Richart, Tom; Ohkubo, Takayoshi; Kuznetsova, Tatiana; Torp-Pedersen, Christian; Lind, Lars; Ibsen, Hans; et al. (The Lancet (British edition), 2007)
Few studies have formally compared the predictive value of the blood pressure at night over and beyond the daytime value. We investigated the prognostic significance of the ambulatory blood pressure during night and day and of the night-to-day blood pressure ratio. We did 24-h blood pressure monitoring in 7458 people (mean age 56·8 years [SD 13·9]) enrolled in prospective population studies in Denmark, Belgium, Japan, Sweden, Uruguay, and China. We calculated multivariate-adjusted hazard ratios for daytime and night-time blood pressure and the systolic night-to-day ratio, while adjusting for cohort and cardiovascular risk factors. Median follow-up was 9·6 years (5th to 95th percentile 2·5–13·7). Adjusted for daytime blood pressure, night-time blood pressure predicted total (n=983; p<0·0001), cardiovascular (n=387; p<0·01), and non-cardiovascular (n=560; p<0·001) mortality. Conversely, adjusted for night-time blood pressure, daytime blood pressure predicted only non-cardiovascular mortality (p<0·05), with lower blood pressure levels being associated with increased risk. Both daytime and night-time blood pressure consistently predicted all cardiovascular events (n=943; p<0·05) and stroke (n=420; p<0·01). Adjusted for night-time blood pressure, daytime blood pressure lost prognostic significance only for cardiac events (n=525; p≥0·07). Adjusted for the 24-h blood pressure, night-to-day ratio predicted mortality, but not fatal combined with non-fatal events. Antihypertensive drug treatment removed the significant association between cardiovascular events and the daytime blood pressure. Participants with systolic night-to-day ratio value of 1 or more were older, at higher risk of death, and died at an older age than those whose night-to-day ratio was normal (≥0·80 to <0·90). In contrast to commonly held views, daytime blood pressure adjusted for night-time blood pressure predicts fatal combined with non-fatal cardiovascular events, except in treated patients, in whom antihypertensive drugs might reduce blood pressure during the day, but not at night. The increased mortality in patients with higher night-time than daytime blood pressure probably indicates reverse causality. Our findings support recording the ambulatory blood pressure during the whole day.